Trend of Antibiotics Usage in the Intensive Care Unit in the Medical City in Baghdad - bijps; Zeena M. Al-Nema (College of Pharmacy University of Baghdad, 2017)
High frequencies of multidrug resistant organisms were observed worldwide in intensive care units which is a warning as to use the only few effective antimicrobials wisely to reduce selective pressure on sensitive strains. The aim of the current study is to asses the compliance of the currently followed antibiotic prescribing pattern in the intensive care unit in an Iraqi hospital with the international guidelines.A cross-sectional study was done in the intensive care unit (ICU) of the Surgical Specialties Hospital, Medical City in Bagdad from the 30th of November 2011 to the 5th of May 2012.Patients were followed until they were discharged or died to see any change in condition, response to drugs, devices used, and medications. During the period of the study, there were 46 patients admitted to the ICU of whom 23 (50%) were males and 23 (50%) were females. The age range of patients was between 16 and 85 years. The mean of age of patients was 44.52 (SDÂ±18.45) years. All patients underwent culture and sensitivity test as soon as they were admitted to the ICU, but out of 46 patients only 16 (34.78%) of them have culture and sensitivity tests results retrieved.The number of patients, in whom the antibiotics were prescribed or changed according to culture and sensitivity tests, was six patients only (13.04%). Ceftriaxone was the most commonly used antibiotic as an empiric treatment followed by ampicillin-cloxacillin combination and meropenem, while clarithromycin and ciprofloxacin were among the least used. The bacterial culture and sensitivity tests of different samples obtained from the patients showed that the most effective antibiotic was tobramycin (90%) followed by ciprofloxacin and levofloxacin (69.2%) for each and the least effective (bacterial resistance) was ceftriaxone (33.3%) and cefotaxime (28.5) among others. In conclusion, there is a critical need for reviewing the trend of antibiotic use in the ICUs depending more on lab. tests to identify the most effective drugs and to minimize the emergence of resistant infection.